Sleep deprivation impairs learning and memory by decreasing protein O‐GlcNAcylation in the brain of adult zebrafish. Issue 1 (27th November 2019) - Lee, Yunkyoung; Park, Jiwon; Kim, Sang‐Min; Nam, Kyunghyun; Lee, Woojoo; Cho, Hyeongjin; Han, Inn‐Oc
Abstract: Sleep is an evolutionarily conserved physiological process implicated in the consolidation of learning and memory (L/M). Here, we report that sleep deprivation (SD)‐induced cognitive deficits in zebrafish are mediated through reduction in O‐GlcNAcylation of brain. Microarray‐based gene expression profiling of zebrafish brain demonstrated significant changes in genes involved in metabolism by SD or fear conditioning (FC), compared to the control group. In particular, it was observed that a marked decrease in the number of genes involved in carboxylic acid and organic acid metabolic processes in the brains of SD group compared to control group. SD downregulated O ‐GlcNAc transferase (OGT) and O ‐GlcNAcylation, while the expression of O ‐GlcNAcase was upregulated. FC activated protein kinase A (PKA) and phosphorylated cAMP response element binding protein (p‐CREB), an effect that was greatly inhibited by SD. Moreover, FC upregulated expressions of OGT and increased O ‐GlcNAcylation in the brains of normal but not SD zebrafish. Intriguingly, upregulation of O ‐GlcNAcylation by glucosamine restored defects in L/M functions and PKA/p‐CREB activity in SD group. Our findings highlight the O ‐GlcNAcylation changes in the brain during the L/M process and further provide a foundation for future studies seeking the molecular and biochemical mechanisms by which HBP of glucose metabolism affects cognitive function.